THE RELATIONSHIP THE RELATIONSHIP BETWEEN THE INTENSITY OF GADGET USE WITH SOCIAL INTERACTION AND EMOTIONAL DEVELOPMENT OF PRESCHOOL CHILDREN (4-6 YEARS): GADGET USE WITH SOCIAL INTERACTION AND EMOTIONAL DEVELOPMENT OF PRESCHOOL CHILDREN (4-6 YEARS) - Anggraeni Setyo Widarto, Tri Anggun; Rahmawati Maulidia; Kurnia Lasana (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
The use of electronic devices among children is increasing. Gadgets are considered safe and easy to supervise by many parents. They often do not consider the negative effects on the development of children's social and emotional interactions. The purpose of this study was to determine the relationship between social interaction and emotional development with the amount of gadget use in preschool children (aged 4-6 years). This type of research is quantitative correlation with a cross-sectional approach. The number of respondents was 68 people with a proportional stratified random sampling method. The research instruments included the SDQ questionnaire, the gadget use intensity questionnaire, and the social interaction questionnaire. The results of this study showed that 43 children (63.2%) used electronic devices in the high category. Hypothesis testing using Spearman Rank produced a p value of 0.000 (less than 0.05) which indicated a relationship between gadget use in preschool children with social emotional development with a correlation between gadget use and social contact of 0.639, emotional development with difficulty of 0.455, and emotional development with strength of 0.418. The conclusion is that there is a relationship between the use of gadgets in preschool children and social emotional development and parents need to be more selective in choosing the toys given to children and monitor and limit the provision of excessive toys.